Y chromosome genetic data defined by 23 short tandem repeats in a Serbian population on the Balkan Peninsula - Tamara Kačar; Gorana Stamenković; Jelena Blagojević; Jovica Krtinić; Dragan Mijović; Damir Marjanović (Annals of Human Biology, 2019)
Background: Serbs mainly live in the territory of the recently re-established state of Serbia. However, the turbulent history in the Balkan Peninsula has led to settlement of Serbs not only within present day Serbia, but also in different parts of neighbouring countries. Aim: To define polymorphisms of 23 Y-chromosomal short tandem repeat (STR) loci in a modern Serbian population from the central part of the Balkan Peninsula. Subjects and methods: The reference sample consisted of 303 men declared as Serbs over three generations. Localities of the collected materials include the territories of Serbia, Bosnia and Herzegovina, Croatia and Montenegro. DNA samples were typed using the PowerPlex®Y23 amplification kit. Results: The highest locus diversity was observed for DYS385 and DYS481. In this study the most abundant haplogroups were I2a, E1b1b, R1a and I1. The largest genetic distances between the Serbs and other close Southern Slavs were for the Macedonians and Slovenians. Conclusion: This study is the first one to define STR polymorphism of Serbian people not only from Serbia but also from other parts of the Balkan Peninsula. The presented genetic data may be useful in further examinations of the genesis and genetic structuring of the present-day Serbian gene pool.